DUKUNGAN KELUARGA MENINGKATKAN SIKAP REMAJA DALAM MENGHADAPI MENARCHE - Hapsari, Puspa; Fadilah, Lola Noviani; Resmana, Rika; Cahyaningsih, Henny (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2024)
As a sign of puberty, menarche is still viewed negatively by adolescents. In addition, menarche occurs at an earlier age which results in a lack of readiness and increases negative attitudes. This negative attitude in facing menarche has an impact on anxiety. The family, as an adolescent's closest environment, needs to provide support to make adolescents have a positive attitude towards menarche. The study aimed to determine the relationship between family support and the adolescent’s attitude facing menarche at Cikancung Elementary School. This research was inferential research with cross-sectional research design. Sampling was carried out using Stratified Random Sampling and sample of 80 adolescents was obtained. The sample in this study were adolescent girls aged 10-13 years in Cikancung Regional Elementary School who had not yet reached menarche. Family support was measured using a valid and reliable questionnaire derived from Friedman's theory and menarche attitudes were measured using the standard AMAQ questionnaire. Data analysis used the Chi-square test. The research results showed that the majority (60%) of respondents received high family support for menarche and the majority (61%) of respondents had a positive attitude towards menarche. There was a relationship between family support and adolescent attitudes towards menarche in Cikancung Elementary School with p-value=0.000 and OR 9.54 or adolescents who received low family support were 9.54 times more likely to have a negative attitude towards menarche. Adolescents positive attitude in facing menarche is related to high family support, therefore families are expected to provide high support regarding menarche to adolescents.